Pengembangan Literasi Geopark Melalui Corner Geopart di Dinas Kearsipan dan Perpustakaan Kabupaten Kebumen - Sundariyati, Dwi; Zain, Labibah (Al-Mamun Jurnal Kajian Kepustakawanan dan Informasi, 2024)
Geopark literacy is the ability to understand and appreciate the geological heritage and the biological, cultural, and social diversity associated with a geopark area. Geopark literacy can be improved through various media and strategies, one of which is the geopark corner. Corner Geopark is a special room in the library that provides information and education about parks through books, brochures, posters, videos, and local products. This study aims to examine the development of geopark literacy through Corner Geopark at the Archives and Library Service (DISARPUS) of Kebumen Regency. The research method uses a qualitative approach by collecting data through in-depth interviews with librarians who have developed Corner Geopark, direct observation, and document analysis. The research location is at the Kebumen Regency Library and Library Office, which is located on Veteran Street No. 1, Kebumen. The results showed that the Geopark Corner at DISARPUS has been running since 2021 and has provided benefits to library visitors, especially students and teachers, and other user communities. Corner Geopark DISARPUS presents information about the Karangsambung-Karangbolong geopark, which according to the latest information is in the process of becoming one of the candidates for UNESCO Global Geopark in Indonesia. Corner Geopark DISARPUS Kebumen is also a means to promote tourism potential and local products in Kebumen Regency. This article recommends that the DISARPUS geopark corner can be improved in quality and quantity by adding a collection of books and other media relevant to geoparks, as well as organizing activities that can increase public interest and participation in geoparks.